Genomic Analysis of KPC-2-Producing Klebsiella pneumoniae ST11 Isolates at the Respiratory Department of a Tertiary Care Hospital in Beijing, China - Guo, Ling; Wang, Lifeng; Zhao, Qiang; Ye, Liyan; Ye, Kun; Ma, Yanning; Shen, Dingxia; Yang, Jiyong (Frontiers in Microbiology, 2022)
Background Carbapenem-resistant Klebsiella pneumoniae (CRKP) is an important pathogen causing hospital-associated outbreaks worldwide. The spread of K. pneumoniae carbapenemase-2 (KPC-2)-producing CRKP is primarily associated with sequence type (ST) 11. Methods A total of 152 KPC-2-producing K. pneumoniae ST11 isolates were collected from the respiratory department of a tertiary care hospital in Beijing, China between 2009 and 2018. The genome sequencing of these isolates was performed on the HiSeq X Ten sequencer. Multilocus sequence typing (MLST), capsular type, plasmid replicon types and resistance genes were identified. Fifteen isolates were selected for the subsequent single-molecule real-time (SMRT) sequencing on the PacBio RS II. Alignment of the complete sequences of the plasmids carrying blaKPC–2 and/or virulence genes was performed by using BRIG and Easyfig. Results From 2012 to 2018, the detection rate of the blaKPC–2-carrying CRKP rose rapidly from 3.3 to 28.1%. KPC-2-producing K. pneumoniae ST11 isolates were dominant in CRKP, which emerged in 2012 and caused several outbreaks. Most isolates exhibited multidrug-resistant to commonly used antibiotics, while all the isolates remained susceptible to tigecycline and polymyxin B. The single nucleotide polymorphism (SNP) analysis showed that all these 152 KPC-2-producing K. pneumoniae ST11 isolates could be divided into three genetically distinct clades (A, B, and C) and eleven subclades (A1–A9 and B1–B2). The majority belonged to clade A with KL47 serotype (n = 117, 77.0%), while KL64 and KL16 were identified in clades B and C, respectively. The blaKPC–2-carrying plasmids exhibited diverse types, namely, IncFII (pHN7A8)/IncR(6/15), IncFII (pHN7A8)/IncpA1763–KPC (5/15), IncFII (pHN7A8) (1/15), IncR (1/15), and IncpA1763–KPC (1/15). The genetic environment of blaKPC–2 showed nine IS26-based composite transposons, which had a basic core structure ISKpn27-blaKPC–2-ΔISKpn6. About 27.6% (42/152) isolates co-carried 2 to 4 virulence marker genes (namely, peg344, iucA, iroB, rmpA, and rmpA2) for hvKp strains. At least three isolates were identified to harbor virulence gene-carrying plasmids. Conclusion KPC-2-producing K. pneumoniae ST11 was highly heterogeneous in our hospital. Transmission of these strains was mainly mediated by twelve high-risk clones. The blaKPC–2-carrying plasmids and genetic environment of blaKPC–2 genes exhibited active evolution in K. pneumoniae ST11. More attention should be paid to the tendency of KPC-2-ST11 to acquire hypervirulent plasmids.